Prední luxace humeru komplikovaná trombózou arteria axillaris--kazuistika - Edelmann, K; Houser, J; Stepánová, E; Obruba, P; Kopp, L (Rozhledy v chirurgii, 2007)
The authors report on a rare complication of humeral luxations, thrombosis of the axillary artery. They present a literature overview to discuss possible causes and mechanisms of venous complications. Although humeral luxations are very frequently diagnosed in traumatological departments, vascular complications are rare. Therefore, thorough examination of every single patient is a must, taking the above possibility into consideration.
Keywords: Shoulder Dislocation; lidé; Thrombosis; arteria axillaris; luxace ramenního kloubu; Aged; Humans; senioři; trombóza; Axillary Artery; ženské pohlaví; Female